The first liquid biopsy test approved. Is it a new era of mutation testing for non-small cell lung cancer? - Kwapisz, Dorota (Ann Transl Med, 2017)
Specific mutations in epidermal growth factor receptor (EGFR) gene are predictive for response to the EGFR tyrosine kinase inhibitors (TKIs) in non-small cell lung cancer patients (NSCLC). According to international guidelines, the molecular testing in patients with advanced NSCLC of a non-squamous subtype is recommended. However, obtain a tissue sample could be challenging. Liquid biopsy allows to determine patients suitable for EGFR-targeted therapy by analysis of circulating-free tumor DNA (cfDNA) in peripheral blood samples and might replace tissue biopsy. It allows to acquire a material in convenient minimally invasive manner, is easily repeatable, could be used for molecular identification and molecular changes monitoring. Many studies show a high concordance rate between tissue and plasma samples testing. When U.S. Food and Drug Administration (FDA) approved the first liquid biopsy test, analysis of driver gene mutation from cfDNA becomes a reality in clinical practice for patients with NSCLC.